Innovator priests from Bahia Blanca. Their trajectories and sociabilities in the crossing between religion and politics in times of social effervescence (1968-1975) - Dominella, Virginia (Sociedad y religión, 2021)
The aim of this article is to reconstruct and to analyse the experience of a group of priests of the Archdiocese of Bahia Blanca, who, in the sixties and seventies, recognised themselves in the ecclesiastical aggiornamento and even with the liberation theology. In particular, it focuses on the trajectories of the participants, their meeting spaces and the nets that were articulated on the fields of liberationist catholicism, the several links they had with the Movement of Priests for the Third World (MSTM), their relations with the hierarchy and their religious-political practices. Who were these presbyters? What were their fields of pastoral action? What were the links they established amongst themselves? How were they a group? What theological and pastoral ideas brought them together? Why only a few of them belonged to the MSTM? What public initiatives they shared when they tried to "embody" their Christian commitment? These are a handful of the questions that order this reflection. A qualitative methodology is used for this paper; and several sources, oral, written and visual, are compared.